JAVANESE HEGEMONY AND INDONESIA-CENTRIC NARRATIVE IN KEMENPAREKRAF YOUTUBE TOURISM VILLAGE VISUAL REPRESENTATION ANALYSIS - Safitri, Lies Utami Efni; Saputra, Rizky (International Journal of Cultural and Social Science, 2025)
This study examines the persistence of Javanese hegemony within the state’s “Indonesia-Centric” tourism narrative, as reflected in the Anugerah Desa Wisata Indonesia (ADWI) 2024 promotional videos on the official Kemenparekraf YouTube channel. Using a mixed-method approach combining quantitative content analysis and semiotic narrative interpretation, this research identifies significant spatial and representational imbalances between Javanese and Non-Javanese destinations. This research analyzes a total of 50 promotional videos (N=50). Quantitative findings reveal that Javanese destinations received 65% of total promotional airtime, with an average duration of 7.22 minutes per video, compared to only 4.57 minutes for Non-Javanese regions. Qualitative analysis further shows that Javanese villages are portrayed through narratives of modernity, accessibility, and managerial excellence framing them as normative and strategic models of success. Conversely, Non-Javanese destinations are represented through exoticized imagery emphasizing remoteness and cultural spectacle, perpetuating the “Othering” discourse. These findings demonstrate a symbolic contradiction between the Indonesia Centric development mandate and the digital execution of tourism branding, where cultural hegemony persists despite decentralization efforts. The study proposes the implementation of an Equity in Promotional Investment (EPI) framework to ensure spatial representational justice and promote genuine inclusivity in Indonesia’s tourism communication strategy.